1998
DOI: 10.1523/jneurosci.18-18-07232.1998
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Calcium and Cell Death during Ischemia in Neonatal Rat White Matter AstrocytesIn Situ

Abstract: The major pathological correlate of cerebral palsy is ischemic injury of CNS white matter. Histological studies show early injury of glial cells and axons. To investigate glial cell injury, I monitored intracellular Ca2+and cell viability in fura-2-loaded neonatal rat white matter glial cells during ischemia. Fura-2 fixation combined with immunohistochemistry revealed that fura-2-loaded cells were GFAP+/O4−and were therefore a population of neonatal white matter astrocytes.Significant ischemic Ca2+influx was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 46 publications
5
84
0
Order By: Relevance
“…While ischemic cell death of pre-myelinating white matter astrocytes is Ca 2 + -dependent (Fern, 1998), we have recently shown that Ca 2 + does not play a role in the death of astrocytes in white matter at a similar developmental stage to those studied here, at least during relatively short periods of ischemia ). In the current study, initial experiments showed that removing Ca 2 + from the extracellular space by perfusing with aCSF to which no Ca 2 + had been added and which contained 70 mmol/L EGTA ('zero-Ca 2 + '), resulted in significant damage to processes at 40 mins (48.374.1% decrease in pixel intensity; n = 5 nerves; P < 0.001) and 60 mins (76.973.1%; P < 0.001; Figures 7A and 7D).…”
Section: The Role Of Ca 2 + In Astrocyte Injurysupporting
confidence: 53%
“…While ischemic cell death of pre-myelinating white matter astrocytes is Ca 2 + -dependent (Fern, 1998), we have recently shown that Ca 2 + does not play a role in the death of astrocytes in white matter at a similar developmental stage to those studied here, at least during relatively short periods of ischemia ). In the current study, initial experiments showed that removing Ca 2 + from the extracellular space by perfusing with aCSF to which no Ca 2 + had been added and which contained 70 mmol/L EGTA ('zero-Ca 2 + '), resulted in significant damage to processes at 40 mins (48.374.1% decrease in pixel intensity; n = 5 nerves; P < 0.001) and 60 mins (76.973.1%; P < 0.001; Figures 7A and 7D).…”
Section: The Role Of Ca 2 + In Astrocyte Injurysupporting
confidence: 53%
“…Astrocytes contain various calcium channels. 37,38,43 The increase in thromboxane formation and calcium signals in astrocytes was inhibited by the selective N-type voltage-gated calcium channel blocker -conotoxin 35 but not by L-type voltage-gated channel blocker nifedipine and putative inhibitor of non-voltage-gated calcium channels SK&F96365. 34 This finding would suggest that in astrocytes, 15-F 2t -IsoP stimulates thromboxane formation by enhancing entry of calcium mainly via N-type voltage-gated calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on receptor-operated and N-as well as L-type voltage-gated Ca 2ϩ channels since endothelial cells are not excitable and are mostly devoid of voltage-gated Ca 2ϩ channels, 36 whereas astrocytes contain voltage-gated channels, primarily of the N-and L-types. 37,38,43 The putative receptoroperated Ca 2ϩ channel blocker SK&F96365 34 selectively reduced TXB 2 formation in endothelial cells, and the selective N-voltage-gated Ca 2ϩ channel blocker -conotoxin 35 caused a similar effect only in astrocytes ( Figure 4); Ca 2ϩ chelator EGTA was effective in both cells. Therefore, TXB 2 formation induced by 15-F 2t -IsoP is dependent on extracellular Ca 2ϩ , which seems to influx through activation of distinct Ca 2ϩ channels in endothelial and astroglial cells.…”
Section: Effects Of 15-f 2t -Isop On Thromboxane Formation By Culturementioning
confidence: 97%
“…The atmosphere in the recording chamber was switched simultaneously to 95% N 2 /5% CO 2 (see Ref. 26 for further details). Ischemia was maintained for 60 min, at which point normal conditions were re-established for a further 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…RONs were maintained in hydrated 95% O 2 /5% CO 2 atmosphere during the incubation period and were washed in aCSF before being mounted in the perfusion chamber. The ends of the optic nerves were fixed to a 22 ϫ 40 mm glass coverslip with small amounts of cyanoacrylate glue, leaving the majority of the nerve completely free of glue (26). The coverslip was sealed onto a Plexiglas perfusion chamber (atmosphere chamber; Warner Instruments) with silicone grease.…”
Section: Intracellular Ca 2ϩ Concentration ([Ca 2ϩ ] I ) Imagingmentioning
confidence: 99%